Assessment of concordance between fresh-frozen and formalin-fixed paraffin embedded tumor DNA methylation using a targeted sequencing approach - Moran, Bruce; Ebert, Matthias; Gaiser, Timo (OncoTarget, 2017)
DNA methylation is altered in many types of disease, including metastatic colorectal cancer. However, the methylome has not yet been fully described in archival formalin-fixed paraffin embedded (FFPE) samples in the context of matched fresh-frozen (FF) tumor material at base-pair resolution using a targeted approach. Using next-generation sequencing, we investigated three pairs of matched FFPE and FF samples to determine the extent of their similarity. We identified a ‘bowing’ pattern specific to FFPE samples categorized by a lower CG proportion at the start of sequence reads. We have found no evidence that this affected methylation calling, nor concordance of results. We also found no significant increase in deamination, measured by C>T transitions, previously considered a result of crosslinking DNA by formalin fixation and a barrier to the use of FFPE in methylation studies. The methods used in this study have shown sensitivity of between 60-70% based on positions also methylated in colorectal cancer cell lines. We demonstrate that FFPE material is a useful source of tumor material for methylation studies using targeted sequencing.
Gesehen am 11.06.2018